ASPEK HUKUM DISKRIMINASI PADA ANAK AKIBAT PERCERAIAN - Hardian Iskandar (Universitas Muhammadiyah Gresik, 2020)
Children are the generation of the nation's administrators, whose growth is protected by the state. As the successor to a protected nation, children in essence need to be avoided from acts of discrimination from divorce that occur between parents so that the child's development and growth can develop both physically, mentally, and socially. This study discusses the legal aspects of discrimination in children based on divorce using the method of discussing normatives, to analyze how the legal aspects of confirmation of divorce children